Technological Innovation to Enhance Access to Information in Rural Communities - Mukhamat Saini; Riza Faishol (STAI Miftahul ULa Nganjuk, 2025)
This study explores the role of technological innovations in enhancing access to information in Sidomulyo Village, Ngadiluwih District, Kediri Regency, East Java. Given the geographical isolation and limited infrastructure in rural areas, the research examines the impact of digital tools—such as mobile health applications, online educational platforms, and agricultural information systems—on improving access to vital resources. The Participatory Action Research (PAR) methodology was employed, involving local stakeholders in the design and implementation of technological solutions. The results indicate significant improvements in educational outcomes, healthcare access, and agricultural decision-making. However, challenges such as limited internet connectivity and digital literacy barriers were also identified. The findings highlight the importance of tailoring technological interventions to local needs and overcoming infrastructural constraints to ensure equitable access. This research provides insights into how technology can be leveraged for sustainable rural development, emphasizing the need for ongoing community engagement and infrastructure improvements..